THE OPTIMIZATION STUDY OF ZSM-5 SYNTHESIS THROUGH STATIC HYDROTHERMAL METHOD WITHOUT ORGANIC STRUCTURE-DIRECTING AGENT - Ayudya Aalstiary, Kania
Zeolite is an aluminosilicate microporous material with a pore diameter of less than 2 nm. Zeolite has high framework stability, good activity and selectivity, and is easy to recycle. Zeolite has high framework stability, good activity and selectivity, and is easy to recycle. Zeolite ZSM-5 has been reported to have unique physicochemical properties, a stable framework and a uniform pore system. Based on these advantages, ZSM-5 is often used in applications such as a catalyst in catalytic fast pyrolysis (CFP) reactions, as an adsorbent in phosphate adsorption, and others. The ZSM-5 zeolite framework consists of pentasil units containing a five-membered rings (5 MRs). In general, the synthesis of ZSM-5 requires tetrapropylammonium ion (TPA+) known as the organic structure-directing agent (OSDA) to help form the framework. However, it requires a high-temperature combustion process to remove organic compounds that can cause environmental pollution. To overcome this problem, the sodium cation (Na+) can act as an inorganic structural-directing agent to substitute OSDA for the synthesis of ZSM-5 is more environmentally friendly. Static synthesis environments are the simplest synthesis condition and depend on natural interactions between precursors. The addition of two-stage aging in the static environments is an effort to obtain a pure ZSM-5 product. The aging stage is expected to help the interaction between precursors to increase the nucleation process. Zeolite synthesis uses a conventional Teflon-coated autoclave with oven heating occurs slow heat transfer and causes a longer synthesis time. Synthesis with tubular autoclaves and oil heating can provide a fast and even heat transfer process over the entire surface. In this study, ZSM-5 was synthesized without OSDA through two-stage aging using conventional autoclaves and tubular autoclaves. The synthesis of ZSM-5 was carried out with a molar composition of 12Na2O : 100SiO2 : 2Al2O3 : 2500H2O. In this research, an optimization study of two-stages aging was conducted with variations in temperature, time, and stirring. Variation of aging temperature was carried out at room temperature and 80 °C. Variations in aging I were carried out for 1 hour, 3 hours and 5 hours and aging II for 12 hours, 24 hours and 36 hours. Aging stirring variations were carried out at a speed of 300 rpm and static. In this research, a one-step aging synthesis was iv carried out with variations in time for 1 hour, 3 hours, and 5 hours and variations in temperature at room temperature and 80 °C. Furthermore, studies on hydrothermal time and temperature using conventional and tubular autoclaves were also carried out. Based on the research results, heating 80 °C at aging I increased the formation rate of zeolite constituent species shown by the sharp peaks of ZSM-5 in the XRD diffraction pattern. The optimization results of the two-stage aging time show that the longer aging time will lead to the formation of another phase. ZSM-5 zeolite can be obtained by aging time I for 1 hour and 3 hours. However, when the aging time I increased to 5 hours there was a magadiite peak in the results of the XRD diffraction pattern. Based on the analysis, the mixed product ZSM-5 and the amorphous phase are formed when the order of two-stages aging has been reversed or when the two-stage aging is in a static state. The stirring at 300 rpm plays a role because it can make the precursor mixture more homogeneous and facilitate chemical reactions between precursors. The optimal condition of aging I was obtained at 80 °C for 1 hour with 300 rpm stirring. The optimal of aging II was obtained at room temperature for 24 hours static. The synthesis through two-stage aging can produce ZSM-5 products more optimal than the synthesis through single-stage aging. Aging II provides a longer time to form zeolite constituent species to accelerate nucleation. Synthesis using a conventional autoclave for 24 hours can produce ZSM-5 with a relative crystallinity of 89% and has a coffin-like morphology. Synthesis using a tubular autoclave at 180 °C resulted in a mixture of ZSM-5 with the magadiite phase. When the temperature was increased to 210 °C, the growth of the magadite phase was inhibited and ZSM-5 was produced with a relative crystallinity of 72%. Higher kinetic temperature can accelerate the ZSM-5 zeolite formation and no other phases. Based on the results of this study, it can be concluded that aging I at 80 °C can increase the formation rate of the zeolite constituent species to accelerate the nucleation process. In this synthesis, hydrated Na+ ions has the same kinetic diameter as the ZSM-5 micropore size, which enables the production of ZSM-5 zeolite products. Synthesis at high temperatures using a tubular autoclave is expected to suppress the growth of impurities and lead to the formation of ZSM-5 zeolite products